Lower limb assessment and anthropometry of adolescent hockey and softball players in talent development programs - Papalia, S.; Penkala, S. (Australian Conference of Science and Medicine in Sport and Third National Sports Injury Prevention Conference: 2003. Tackling the barriers of performance and participation, 2003)
The purpose of this study was to evaluate and compare the anthropometric and lower limb musculoskeletal assessment profiles of adolescent hockey and softball players. Subjects were: Hockey - 14 males, 17 females; mean age 14.2 years, range 13 to 15 years and Softball - 12 males, 12 females; mean age 13.4 years, range 13 to 14 years; in talent development programs. Assessment consisted of: hip, knee and ankle range of motion; muscle tightness measurement for both limbs; Anthropometric profile; training, competition and lower limb injury/pain history. The two groups of athletes did not differ in years playing their sport however the softball players reported significantly higher hours of training and competition per week (p<0.05). (Softball: Training 7.6+4.4 hrs, Competition 3.1+2.2 hrs; Hockey: Training 4.9+3.0 hrs, Competition 2.7+1.4 hrs). Hockey players exhibited: significantly (p<0.05) lower hip internal/external rotation ranges; significantly (p<0.05) tighter gastrocnemius and soleus muscles; and higher Beighton whole body hyper mobility scores when compared to Softball players. Analysis of anthropometric data revealed that the female hockey and softball players differed significantly in triceps, biceps, front thigh, medial calf and sum of 7 skinfolds (Ó of 7 Skinfolds: Hockey 106.9+34.6 mm, Softball 136.9 +44.6 mm) and relaxed arm girth (Hockey 24.7+1.5 mm; Softball 26.9+2.9 mm). Male Hockey and Softball player`s anthropometric measures did not differ. The most common injury site was the knee for hockey (39% of injuries) and ankle for softball (21% of injuries). Pain on exercise was most frequently reported at the knee for both hockey and softball.